Efficiency of Iron- and Calcium-Impregnated Biochar in Adsorbing Phosphate From Wastewater in Onsite Wastewater Treatment Systems - Dalahmeh, Sahar S.; Stenström, Ylva; Jebrane, Mohamed; Hylander, Lars D.; Daniel, Geoffrey; Heinmaa, Ivo (Frontiers in Environmental Science, 2020)
This study evaluated the potential of biochar impregnated with Fe3+ or Ca2+, or mixed with Polonite®, as a filter material for removal of phosphate (PO4-P) from wastewater in onsite wastewater treatment systems (OWTS). Four treatments with biochar were investigated: unimpregnated biochar (UBC), biochar impregnated with iron Fe3+ (FBC), biochar impregnated with calcium oxide (CBC), and biochar mixed with Polonite® (PBC). In a batch experiment using phosphate solution at concentrations 0.5, 3.3, 6.5, 13, and 26 mg PO4-P L-1, adsorption of PO4-P in the different treatments was modelled using Langmuir and Freundlich isotherms. Column filters (5 diameter × 55 cm height) packed with UBC, FBC, CBC, and PBC were then furnished with raw wastewater over 148 weeks. During this experiment, adsorption of PO4-P was investigated in response to increasing hydraulic loading rate (HLR; 56, 74, and 112 L m-2 day-1) and increasing phosphate loading rate (PLR; 195, 324, 653, and 1715 mg PO4-P m-2 day-1). Among the materials, FBC had the highest maximum adsorption capacity (Qm) based on Langmuir isotherms (3.21 ± 0.01 mg g-1). FBC and CBC showed robust performance with increasing HLR, while increasing PLR increased the amount of PO4-P retained in all filters. After 148 weeks of operation, removal of PO4-P (averaged over the last 18 weeks of operation) was 13 ± 16 % for UBC, 40 ± 20 % for CBC, 88 ± 12 % for FBC, and 30 ± 18 % for PBC. The PO4-P amount retained in filters over the 148 weeks was 84.75, 221.75, 358.38, and 152.36 g m-2 in UBC, CBC, FBC, and PBC, respectively. The adsorption capacity of the filters after 148 weeks was 1.50, 4.02, 6.41, and 2.75 mg g-1 for UBC, CBC, FBC and PBC, respectively. The adsorption capacity values and breakthrough curves showed that low concentrations (i.e., <2.6 mg L-1) of PO4-P in wastewater would allow the FBC filter to remain active for 58 months and the CBC filter for 15 months, before PO4-P removal declined to <70 %. In conclusion, biochar impregnated with iron and calcium is a promising solution for removal of PO4-P from wastewater in OWTS.